[LB.03.12] THE USE OF CARDIOVASCULAR PREVENTION DRUGS IN SUBJECTS AFTER STROKE OR TIA. A POPULATION STUDY. (September 2017) - Redon, J.; Uso, R.; Trillo, J.L.; Fernandez, A.; Morales, F.; Orozco, D.; Gil, V.; Sanchis, J.
Abstract : Objective: Drug treatment for secondary prevention of cardiovascular disease is an establish strategy recommended by guidelines. However, a wide gap exists between what the guidelines say and the real life in terms of number of drugs. The objective of the SATURNO study was to assess what is the gap in subjects after stroke or transitory ischemic attack (TIA) based on Electronic Health Records (EHR). Design and method: Patients with a diagnosis of stroke or TIA before to January 1st, 2012 were selected from the EHR of the Valencia Community which contain all drug prescriptions. In the present study, three groups of therapy usually recommended for secondary prevention or for control of main cardiovascular risk factors were selected: aspirin, SRA blockers (ACEi or ARB) and statins. Assessment of treatment was performed after 5.3 + 3.3 yr of the event. Results: A total of 164315 patients (50% women, mean age 73 yr) were included, 130053 and 34259 with stroke and TIA, respectively. Among them, 41521 (25%) were not taking drug of the three groups, 25679 (168%) one, 45069 (27%) two and 51828 (32%) three. Concerning the kind of drugs, aspirin was present in 58%, followed by 57% SRA blockers and 48% statins. The percentage of number of drugs used and the specific groups in a previous diagnosis of stroke or TIA is in the figure. Figure. No caption available. Conclusions: The proportion of patients taking cardiovascular preventive drugs after a stroke of TIA is low in the general population, even aspirin. Several factors can contribute to it, but physician inertia and low patient compliance requires action in order to improve the secondary prevention.